The Influence of Physical Factors, Social Factors and Psychological Factors on Employee Job Satisfaction - Natsir, Uhud Darmawan (Nusantara Economics and Entrepreneurships Journals, 2025)
This study aims to determine the effect of Physical, Social, and Psychological Factors on Employee Job Satisfaction at PT. Cahya Vidi Abadi in Banyuasin Regency. simultaneously and partially. The type of research used is associative research. The population in this study amounted to 90 permanent employees and the sample used was 74 employees with a Proportionate Stratified Random Sampling sampling technique. The data used in this study are primary data and secondary data. The data collection technique used is the questionnaire and documentation method. The analysis technique used in this study is multiple linear regression analysis, F test, t test and coefficient of determination with a significance level of 5%. The results of the study indicate that 1) There is a positive and significant effect of Physical, Social, and Psychological Factors on Employee Job Satisfaction at PT. Cahya Vidi Abadi in Banyuasin Regency, 2) There is a positive and significant effect of Physical Factors on Employee Job Satisfaction at PT. Cahya Vidi Abadi in Banyuasin Regency, 3) There is a positive and significant effect of Social Factors on Employee Job Satisfaction at PT. Cahya Vidi Abadi in Banyuasin Regency, 4) There is a positive and significant influence of Psychological Factors on Employee Job Satisfaction of PT. Cahya Vidi Abadi in Banyuasin Regency.